SIKAP PETANI TERHADAP KEGAGALAN PRODUKSI USAHA TANI PADI SAWAH DI DESA MAGEPANDA, KECAMATAN MAGEPANDA KABUPATEN SIKKA - Sarlina Noni (Universitas Wiralodra, 2019)
Efforts to increase food production always receive attention because the need for rice continues to increase. The purpose of this study was to determine the effect of factors forming attitudes with the attitude of farmers to the failure of production of lowland rice farming in Magepanda Village, Magepanda Subdistrict, Sikka District. The type of research used in this study is quantitative descriptive research and correlation. Quantitative is data that is measured in a numeric (number) with the aim of testing a predetermined hypothesis. The data used in this study are primary data. Based on the results of data analysis, it can be concluded that the attitude of farmers towards production failure in the farm group of Desa Magepanda, using the fishbein analysis method based on six attributes obtained an average score of 85.17 which is categorized as positive. This means that the attitude of farmers in the Magepanda village farmer group accepts production failure as a motivation for the sustainability of their production activities. The results of the Analysis of Determination Coefficient (R2) are 0, 185 which means that the contribution of the variable farmer attitude (X) to production failure (Y) in the farmer group in Magepanda Village is 18.5%. while the remaining 81.5% is explained by other variables not included in this research model. The results of simple linear regression analysis can be seen that the farmer attitude variable (X) is obtained: -2,613 <- 2,042, so Ho is rejected and Ha is accepted, meaning that the attitude of farmers (X) has a significant effect on production failure (Y).